The origin of the enhanced activity of Pt/zeolites for combustion of C2-C4 alkanes - Garetto, Teresita Francisca (2007)
The deep oxidations of ethane, propane and butane were studied on Pt supported on MgO, alumina, and zeolites KL, HY, ZSM5, and Beta. The catalyst activities were evaluated through both conversion versus temperature (light-off curves) and conversion versus time catalytic tests. The Pt oxidation activity for the three lower alkanes was drastically increased when supported on zeolites as compared to Pt/Al2O3 or Pt/MgO. C2-C4 alkane oxidation turnover rates were about two (ethane, propane) and one (butane) orders of magnitude higher on Pt/acid zeolites than on Pt/Al2O3, but also weakly acid Pt/KL zeolite was significantly more active as compared to Pt/Al2O3 (more than one order of magnitude for ethane and propane). This latter result showed that the support acidity is not a major contributing factor for lower alkane combustion. Promotion of the alkane oxidation activity on Pt/zeolites was explained by considering the drastic increase observed for the density of alkane adsorbed species on zeolite supports; it was found, in fact, that the alkane uptake per m2 was about one order of magnitude higher on Pt/zeolites than on Pt/Al2O3. This alkane confinement in zeolite pores would enhance the Pt oxidation rate because the reaction is positive order with respect to the hydrocarbon and probably also because would promote an additional oxidation pathway in the metal-oxide interfacial region.